Analysis of Aging Society in Thailand between A.D. 2016-2022 - Phungviwatnikul , Weena; Voraprateep, Jutharath (Journal of Arts and Thai Studies, 2024)
Objectives: This research article objectives are to analyze the aging society in Thailand between A.D. 2016-2022, to study problems and solutions to aging society in Thailand and to suggest guidelines for the preparation of the aging society in Thailand at present and future. Methods: This research is qualitative research using documentary research and has taken numbers, statistics, various problems, regulations, orders, laws of aging society in Thailand from the Department of Older Persons, Ministry of Social Development and Human Security between A.D. 2016-2022. Results: The research results were summarized as follows: (1) in 2021, Thailand is a completely aged society that population aged 60 years and over is up to 20 percent of the total population, in 2031, Thailand will be a super-aged society that population aged 60 years and over is up to 28 percent of the total population (2) the aging society problems in Thailand are divided into 4 aspects: economic, social, health, and environment, the example of common health problem is falls because of the physical characteristic of the elderly which is caused by various diseases such as cardiovascular disease etc. and (3) the government should have guidelines to support the rapidly older persons in the future, for example encouraging more employment of the elderly, and there is a sector to monitor the needs of employers and employees to suit the expertise of each type of work, etc. Application of this study: This study can be used as a guideline for preparing and dealing with the aging society in Thailand at present and future, as well as providing social welfare and improving the quality of life of the elderly.